Study on the transient response of lower limb rehabilitation actuator using the pneumatic cylinder - Duc Mịnh Dao; Phuoc Dang Pham; Tuy Xuan Tran; Tram Thi Thuy Le (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2018)
A lower limb rehabilitation device was designed using the compressed air cylinder in order to answer the particular request in Vietnam. This paper is presenting the results of a study of the device response. Dynamic equation of the actuator and equations of the proportional valve have been established. The relationship between the input signal and the output signal of the actuator was derived. Inventor® software was used to design the mechanical structure of the device. Matlab® software was used to calculate the parameters values of the PID controller by simulating the response of the actuator. The results show that the response time of both knee drive and hip drive mechanisms are 8 seconds while the overshoot of both knee drive and hip drive mechanisms are 1%. Moreover, the starting torque of the knee drive mechanism is 17 Nm, and the starting torque of the hip drive mechanism is 35 Nm. The simulation results show that the PID controller gives a fast response time and a low overshoot.